Shark movements between islands in the Revillagigedo Archipelago and connectivity to other islands in the Eastern Tropical Pacific - Frida Lara-Lizardi; James T. Ketchum; Alex R. Hearn; A. Peter Klimley; Felipe Galván-Magaña; Alex Antoniou; Randall Arauz; Sandra Bessudo; Eleazar Castro; Elpis J. Chávez; Eric E.G. Clua; Eduardo Espinoza; et al. (PLoS ONE, 2026)
There is a need to understand the degree to which sharks move between islands in Marine Protected Areas (MPAs) of the Eastern Tropical Pacific (ETP). Exposure to fishing activities becomes significant when no-take zones do not cover the critical areas that sharks use. We analyzed an ultrasonic telemetry dataset to assess how Galapagos sharks ( Carcharhinus galapagensis ) and silky sharks ( Carcharhinus falciformis ) move between the islands that comprise the Revillagigedo Archipelago (RA) and how they migrate to other islands in the ETP. In total, 92 sharks of both species were tracked from January 2010 to December 2018 in the region. Particularly, 39 sharks were detected in the Revillagigedo Archipelago (RA). Of these, 27 were resident at one island (behavior type I), 10 moved between two or more islands within a MPA (type II), and 3 sharks moved between MPAs (behavior type III): a silky shark tagged at Roca Partida (RA) that moved to Clipperton Atoll (CA), another silky shark moved from Wolf, Galapagos Archipelago (GA) to CA and back again and a Galapagos shark tagged at Socorro Island (RA), detected at CA, and finally recorded in Darwin Island (GA). This excursion was one of the longest movements ever recorded for the species (3,160 km). The long-distance dispersal observed in these two species underscores the necessity for international collaboration. Such cooperation is essential to implement effective shark protection measures, including swimways or MigraVías , and other conservation tools in the ETP region.